From lab to forest: overcoming barriers to in vitro propagation of forest trees - Aronen, Tuija; Sota, Valbona; Cvjetković, Branislav; Christie, Bruce; Rupps, Andrea; Fischerova, Lucie; Rathore, Dheeraj Singh; Werbrouck, Stefaan P. O. (Springer Nature, 2025)
Reforestation initiatives are often limited by insufficient seeds, a problem exacerbated by natural variability in tree flowering and seed production and climate change and other environmental challenges. Innovative and adaptive solutions such as in vitro propagation are thus needed. Tissue culture can provide high-quality propagation material for tree conservation and mass propagation, but faces technical, economic, regulatory, and social barriers. Obstacles related to the academia–industry interface and to stakeholder concerns are discussed and actions suggested to overcome these barriers to realize the full potential of tree micropropagation. These include refining techniques to improve efficiency and reduce costs; establishing collaborations among researchers, industry, and foresters; and reducing points of contention and misinformation regarding genetic diversity and public perception. International collaborative initiatives, exemplified by the EU COST Action CA21157 COPYTREE, are elementary for achieving these goals.
Keywords: commercialization; forest reproductive material; technology transfer; tissue culture